Nitric oxide is not a negative regulator of metamorphic induction in the abalone Haliotis asinina - Ueda, Nobuo; Degnan, Sandie M. (Frontiers in Marine Science, 2014)
Nitric oxide (NO) is a second messenger molecule synthesized by the enzyme nitric oxide synthase (NOS) that requires the molecular chaperone heat shock protein 90 (HSP90) for normal enzymatic activity. Past studies have revealed that both NO and HSP90 act as negative regulators (repressors) of metamorphosis in a diverse range of marine invertebrates, including several molluscan species. Here, we test the role of NO in the metamorphic induction of a vetigastropod mollusc, the tropical abalone Haliotis asinina. Specifically, we 1) test the effects of NO-manipulating pharmacological agents, 2) measure the temporal expression of NOS and HSP90 genes through metamorphosis, and 3) assess the spatial expression of NOS and HSP90 in larvae. We find that inhibition of NOS reduces rates of metamorphosis, indicating that NO facilitates, rather than represses, induction of metamorphosis in H. asinina. The marked increase in NOS expression in putative sensory cells localized to the anterior foot of competent larvae is consistent with NO as an inductive molecule for metamorphosis. In contrast to NOS, HSP90 transcript abundance decreases at competence and there is no evidence of NOS and HSP90 transcript co-localization. This study provides the first evidence of NO as an inductive facilitator of molluscan metamorphosis. Our experimental data suggest that NO modulates signals derived from live inductive substrates via the larval foot to regulate metamorphosis. Inter-specific comparisons of spatial NOS expression in molluscs suggest that the localized pattern of NOS or its protein product is related to the regulatory action of NO in metamorphosis.